2017
DOI: 10.1007/s11904-017-0347-y
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Aging in Older Women Living with HIV Infection: a Systematic Review of Psychosocial Factors

Abstract: Due to life-enhancing effects of antiretroviral therapy, HIV-positive persons have the potential for long life comparable to their uninfected peers. Older women (age 50+) living with HIV (OWLH) are often an under-recognized aging group. We conducted a systematic review to examine psychosocial factors that impact how OWLH live, cope, and age with HIV. Initial key word search yielded 1527 records, and 21 studies met our inclusion criteria of original quantitative or qualitative research published between 2013 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…With advancing age comes the pursuit of medical care for typical age-related complications ranging from menopause and rheumatoid arthritis to cognitive decline. Research in older adults with HIV suggest psychosocial factors such as stigma and depression might delay the seeking-out of health care, hamper appointment attendance (Emlet, 2006; Grov et al, 2010; Havlik et al, 2011; Pence et al, 2018; Rodriguez-Penney et al, 2013; Rubtsova et al, 2017; Sankar et al, 2011; Shippy & Karpiak, 2005). While negative psychosocial interactions for aging are expected, a meta-analysis highlighting a dozen studies of older adults with HIV revealed decreased short- and long-term risk for non-adherence to HAART, suggesting that some aspects of HIV self-care may be enhanced with older age (Ghidei et al, 2013).…”
Section: Cardiovascular Disease and Psychosocial Riskmentioning
confidence: 99%
“…With advancing age comes the pursuit of medical care for typical age-related complications ranging from menopause and rheumatoid arthritis to cognitive decline. Research in older adults with HIV suggest psychosocial factors such as stigma and depression might delay the seeking-out of health care, hamper appointment attendance (Emlet, 2006; Grov et al, 2010; Havlik et al, 2011; Pence et al, 2018; Rodriguez-Penney et al, 2013; Rubtsova et al, 2017; Sankar et al, 2011; Shippy & Karpiak, 2005). While negative psychosocial interactions for aging are expected, a meta-analysis highlighting a dozen studies of older adults with HIV revealed decreased short- and long-term risk for non-adherence to HAART, suggesting that some aspects of HIV self-care may be enhanced with older age (Ghidei et al, 2013).…”
Section: Cardiovascular Disease and Psychosocial Riskmentioning
confidence: 99%
“…Proposed here is a conceptual framework that incorporates the relevant data from the field as summarized above to describe determinants of health-related quality of life for older aged PLWH in rural sub-Saharan Africa (Figure 2). The framework incorporates a syndromic approach to gerontology (Fried et al, 2001; Mitnitsky, Mogilner, & Rockwood, 2001) to include domains of physical, cognitive, and social functioning (Rubtsova et al, 2017; Thurn & Gustafson, 2017). It includes key determinants of these domains derived from prior work on HIV and aging in the United States, which have demonstrated independent effects of HIV-related inflammation on domains of physical and neurocognitive functioning (Erlandson et al, 2013; Lyons et al, 2011; Scully et al, 2016).…”
Section: A Conceptual Framework For Aging With Hiv In Sub-saharan Africamentioning
confidence: 99%
“…Psychosocial factors have been shown to influence adherence to medical care, disease progression, and quality of life for people living with HIV (Malow et al, 2013;Reif et al, 2011;Sumari-de Boer et al, 2012). Because psychosocial factors may also be more malleable than many social determinants of health (e.g., education, economic stability), understanding the psychosocial needs of vulnerable HIV populations is critical to developing interventions that aim to improve their overall well-being (Rubtsova et al, 2017). While most of the current research on aging and HIV is focused on biomedical processes and outcomes (e.g., HIV-associated neurocognitive disorder, impacts of long-term ART use), understanding psychosocial aspects of aging with HIV is equally important (Altschuler et al, 2004), especially because psychosocial factors such as social support or spiritual beliefs may help to mitigate impacts of HIV-related stigma (Porter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent systematic review of interventions designed to increase ART adherence among people living with HIV, only 11 out of 49 studies explored psychosocial variables as outcomes (Mbuagbaw et al, 2015). Similarly, Rubtsova et al (2017) reviewed 21 studies that evaluated the psychosocial wellbeing of older women living with HIV and suggested insufficient data and unclear patterns of how older women cope and age with HIV. To the best of our knowledge, there has not yet been a comprehensive literature review of psychosocial interventions that are specifically designed to promote well-being and enhance quality of life among older adults living with HIV.…”
Section: Introductionmentioning
confidence: 99%